Trend and Factors Associated with Repeat Computed Tomography Examinations in Tertiary Hospitals: Linked Health Administrative Data in Western Australia - Ninh Ha (International Journal of Population Data Science, 2020)
Introduction Computed tomography (CT) has become an essential part of clinical practice. However, repeat CT scans has raised a concern about unnecessary exposure to ionising radiation and waste of health care resource. While substantial effort is underway to reduce inappropriate use of diagnostic imaging tests including CT, little evidence of any change in repeat CT use and its associated factors.